Spirometric values and chest pain intensity three days post-operative coronary artery bypass graft surgery - AlOtaibi, Kholoud D (Journal of the Saudi Heart Association, 2015)
AIM: Coronary artery bypass graft surgery (CABG) is proved to have ventilatory complications and reduction in spirometric values. This study aimed to examine the hypothesis that reduction of post-operative chest pain intensity would be associated with improvement in the spirometric values for patient underwent CABG